International tourist satisfaction and dissemination information towards Kampung Banghuris Homestay attributes / Laya Morajab - Morajab, Laya (2010)
This study analyzed the relationship between home stay attributes towards international tourist satisfaction and dissemination information in Kampung Banghuris Homestay, Selangor. Tourist perception of the home stay attribute, satisfaction with their experience caused the dissemination information and these items are vital for successful destination management. Moreover destination attributes affect the perceived quality of tourist offerings, which positively relates to satisfaction as well as visitors loyalty and dissemination information. Nevertheless, there are other factor which are also significant such as type of building, feature of equipment, host family’s empathy and responsiveness and moreover feel of safety and security at the destination. Data was gathered by self-administered questionnaire at Kampong Banghuris Homestay. The analysis strongly supported the assumption of a positive relationship between home stay attributes and international tourist satisfaction. Furthermore, tourist satisfaction significantly contributed to the prediction of intention to return as well as homestay attributes was found significantly influence the tourist’s intention to return and tourist satisfaction demonstrates a mediating effect towards the relationship between homestay attributes and dissemination of information. The findings of this study provide a valuable tools and recommendation to increase international tourists’ satisfaction with Kampung Banghuris Homestay. A thorough understanding of tourists’ expectation and satisfaction will assist homestay managers to provide better services to their customers, to identify their faulty and weaknesses and to understand the characteristics and behaviors of tourists visiting homestay. Moreover identifying the attributes which affects satisfaction level of the international tourists who visit homestay will help tourism planners develop appropriate strategies to attract more customers and to serve them successfully.